Antibacterial Activity of Terminalia mantaly Stem Ethanol Extract as Hand Sanitizer Gel - Sovia, Evi; Sujono, Hernandi; Farizi, Rinaldi; Sutrisno, Sutrisno; Nurhadianti, Adilfi Risma; Yun, Yenny Febriani (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Hand sanitizers generally contain alcohol. However, it can cause dry and irritated skin. Therefore, it is necessary to find antibacterial alternatives that are safe for the skin. One of the plants that has antibacterial activity is Terminalia mantaly (T. mantaly). This study aimed to investigate the antibacterial activity of ethanol extract and hand sanitizer gel of T. mantaly.Methods: The antibacterial activity test against gram-positive (Staphylococcus aureus and Streptococcus pyogenes) and gram-negative bacteria (Escherichia coli and Shigella dysenteriae) was carried out using the liquid micro dilution method. The phytochemical tests were also performed. This study was conducted at the Chemistry Laboratory, Faculty of Sains and Informatics, Universitas Jenderal Achmad Yani in April-June 2022.Results: The ethanol extract of T. mantaly stem contained secondary metabolites of alkaloids, tannins, quinones, saponins, steroids, and flavonoids. The minimum inhibitory concentration (MIC) values of T. mantaly stem ethanol extract against Escherichia coli, Shigella dysenteriae, Staphylococcus aureus, Streptococcus pyogenes were 0.63%, 0.63%, 0.16%, and 0.16%, whereas the hand sanitizer gel gave MIC values of 0.63%; 0.31%; 0.16%; and 0.16% respectively. The minimum bactericidal concentration (MBC) values of T. mantaly stem ethanol extract and hand sanitizer gel had the same results, namely 2.50%, 0.16%, 1.25%, and 1.25%. The physical stability of the hand sanitizer gel from the ethanol extract of T. mantaly stem met the physical stability standards of the gel. Conclusions: The ethanol extract of the T. mantaly stems has stronger antibacterial activity against gram-positive bacteria than against gram- negative bacteria.